The Athenian Empire and epigraphic cultures - Lazar, L (Cambridge University Press, 2024)
This article revisits the question of how the epigraphic culture of the fifth-century BC Athenian empire impacted on the epigraphic cultures of other communities. Through consideration of the late fifth-century epigraphic cultures of Thasos and Rhodes, it argues that allied communities interacted with the epigraphic manifestations of Athenian authority in different ways, producing diverse epigraphic responses. Further, it argues that the first traces of the shift from the heterogeneity of Archaic epigraphic cultures to the epigraphic convergence of the late Classical world can be found in the tension between local and Athenian influences in late fifth-century public inscription beyond Athens.